Prediction method and application of the effective period of oil and gas formation by transport of oil source fault - Wen, Huijian; Wang, Chao (Frontiers in Earth Science, 2025)
The effective period of hydrocarbon formation has a significant impact on oil and gas enrichment. Based on an analysis of the mechanism of oil and gas formation by oil source fault transport, the transport period is determined by both the activity period of the oil source fault and the discharge period of oil and gas from the source rock. A set of predictive methods for oil and gas formation by oil source fault transport has been developed by combining of the oil source fault transport and the start of the period for oil and gas aggregation. The results show that the results show that this method is operationally feasible and yields reliable predictions. The effective period of Dazhangtuo fault transport in relation to oil and gas formation in the lower sub-member of the first member of the Shahejie Formation is half of the period of oil and gas expulsion from source rocks of the third member of the Shahejie Formation, which is more favorable for the migration of hydrocarbons from the third member source rocks, facilitating oil and gas accumulation in the lower sub-member of the first member of the Shahejie Formation. This is the main reason why drilling in the lower sub-member of the first member of the Shahejie Formation of the Dazhangtuo fault has revealed that oil and gas are mainly concentrated in the eastern part, with only small amounts found in the western part.